Demolishing myths or mosques and temples? : readings on history and temple desecration in medieval India - Kumar, Sunil (Three Essays Collective, 2008)
History, it is said, cannot be studied without reflecting on the practice of historians who narrate it. The articles in this volume introduce readers to the writings of four scholars who study the subject of temple desecration in interesting and different ways. They focus on the ways in which historians study the political culture, events, historical narratives, material remains and aesthetic norms of a time very distant from us. Through their focus on the theme of temple desecration, a subject of considerable import in political rhetoric today, these essays also underline how easily history can be subverted to serve narrow, cynical ends. At a time when history has become so important in the making of the nation’s identity, the articles in this book invite the readers to pause and reflect on the craft of history, the exciting and engaging conclusions to which it can lead and the worrying ends to which it can also be nudged.